Electrophoretic Deposition and Characterization of HA/Chitosan Nanocomposite Coatings on Ti6Al7Nb Alloy - Moskalewicz, Tomasz; Kot, Marcin; Seuß, Sigrid; Kedzierska, Aleksandra; Czyrska-Filemonowicz, Aleksandra; Boccaccini, Aldo R. (Metals and Materials International, 2015)
Nano-hydroxyapatite/chitosan (nc-HA/chitosan) composite coatings were produced on two phase (alpha+beta) Ti6Al7Nb titanium alloy substrates by electrophoretic deposition (EPD). The microstructure of the coatings was examined by scanning- and transmission electron microscopy methods as well as by X-ray diffi-actometry. The coatings, 770 nm - 800 nm thick, were uniform, without any cracks or presence of large voids and they exhibited good adhesion to the titanium alloy substrate. The microstructure of the coatings consisted of nc-HA needle-like particles homogeneously embedded in a chitosan matrix. The deposited coatings exhibited good adhesion to the substrate. The best adhesion to the titanium alloy was determined for the coating deposited from suspensions containing 4 g/L of HA at 10 V during 240 s. The results confirm EPD as a convenient method to develop uniform and crack-free nanoscale organic-inorganic composite coatings on two phase titanium alloy substrates with potential application in orthopedic and dental implants.
Keywords: biomaterials; coating; surface modification; microstructure; transmission electron microscopy (TEM)